Calcareous nannofossil assemblages around the Pliensbachian/Toarcian boundary in the reference section of Peniche (Portugal) - Veiga de Oliveira, L. C. (2007)
The Pliensbachian/Toarcian boundary (Lower Jurassic) is well represented in the Lusitanian Basin (Portugal), mainly in the Peniche area, recorded by a marl/limestone series. Calcareous nannofossil assemblages are described herein, with the aim to contribute to the Toarcian GSSP definition. Marly samples were collected 3 m below and 7 m above this boundary and analysed for calcareous nannofossils. The main nannofossils observed were Biscutum finchii, B. grande, Calcivascularis jansae, Crepidolithus crassus, C. granulatus, C. impontus, Lotharingius hauffii, L. sigillatus, L. aff. L. velatus, Schizosphaerella spp. and Tubirhabdus patulus. This assemblage indicates that the Pliensbachian/Toarcian boundary in Peniche lies in the upper part of the NJ5b Subzone. Schizosphaerella and Lotharingius dominate the assemblage. The abundant occurrence of C. jansae and the common occurrence of B. grande indicate a strong Tethyan influence.